Étude de la main-d'œuvre agricole dans la région d'El Oued - OUSSAMA LEJDEL Ali; AZEB CHIKH Abd El Krim (University of Eloued جامعة الوادي, 2025)
Our study is a diagnostic and analytical study of the agricultural labor force in the El Oued region, examining it from all aspects. We interviewed 176 agricultural workers in various agricultural areas in the El Oued province: : Magrane, Debila, Robbah, Bayadha, Reguiba, Ourmes, Oued El Alenda, Douar El Maa, Guemar, Hassi Khalifa, Sidi Aoun, Ben Guecha, Mih Oans). We analyzed the survey data from all aspects, including gender, marital status, age, knowledge of age groups, and educational level of agricultural workers in this region. Among these aspects, we studied the largest segment of agricultural workers, their working hours, the tasks they perform, the nature of their activity, their seasons, the types of agricultural workers, and their methods of wages, among other things. Based on this, and after analyzing the survey results, we were able to understand several characteristics of the .agricultural labor sector and its working conditions in the El Oued region
Keywords: Agricultural labor; El Oued region; agriculture